Recession and Policy Transmission to Latin American Tourism : Does Expanded Travel to Cuba Offset Crisis Spillovers? - Wolfe, Andy.; Romeu, Rafael (Washington, D.C. : International Monetary Fund, 2011)
This study measures the impact of changing economic conditions in OECD countries on tourist arrivals to countries/destinations in Latin America and the Caribbean. A model of utility maximization across labor, consumption of goods and services at home, and consumption of tourism services across monopolistically competitive destinations abroad is presented. The model yields estimable equations arrivals as a function of OECD economic conditions and the elasticity of substitution across tourist destinations. Estimates suggest median tourism arrivals decline by at least three to five percent in response to a one percent increase in OECD unemployment, even after controlling for declines in OECD consumption and output gaps. Arrivals to individual destination are driven by differing exposure to OECD country groups sharing similar business cycle characteristics. Estimates of the elasticity of substitution suggest that tourism demand is highly price sensitive, and that a variety of costs to delivering tourism services drive market share losses in uncompetitive destinations. One recent cost change, the 2009 easing of restrictions on U.S. travel to Cuba, supported a small (countercyclical) boost to Cuba's arrivals of U.S. non-family travel, as well as a pre-existing surge in family travel (of Cuban origin). Despite the US becoming Cuba's second highest arrival source, Cuban policymakers have significant scope for lowering the relatively high costs of family travel from the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet